Identification and Characterization of Rat RhoA Gene Promoter - Yoshihiko Chiba; Kumiko Goto; Kimihiko Matsusue; Shioko Kimura; Miwa Misawa (Elsevier, 2010)
RhoA upregulation has been suggested in bronchial smooth muscles (BSMs) of asthmatic rats. Here, we cloned/characterized the 5'-promoter region of the rat rhoA. A transcription-initiation site was identified at 66-bp upstream of the reference sequence, GenBank-BC061732. Luciferase assay using interleukin-13 (IL-13)-stimulated cells revealed a significant promoter activity at 238- to 166-bp upstream of the transcription-initiation site, which contains a signal transducer and activation of transcription (STAT) 6-binding region. The IL-13-induced increase in luciferase activity was inhibited by a STAT6 inhibitor, AS1517499, or a Janus kinases (JAKs) inhibitor, JAK Inhibitor-I, but not by tyrphostin-AG490, WHI-P131, or tyrphostin-AG9 (selective JAK2, JAK3, and Tyk2 inhibitors, respectively). Thus, rat BSM rhoA expression may have causal relation to the IL-13-JAK1-STAT6 signaling. Keywords:: RhoA, transcriptional regulation, bronchial smooth muscle